The Dynamics of Family Law Reform in Asia and Africa (Portrait of Polygamy Regulations in Indonesia, Malaysia, Pakistan, Morocco and Tunisia) - Noviana, Lia; Wigati, Risma; Sakdiyah, Nurulaini Halimatus (Al-Syakhsiyyah: Journal of Law & Family Studies, 2022)
One of the most widely promoted family law reforms in modern Muslim countries is the issue of polygamy. Until now, polygamy is considered as a form of discrimination and marginalization of women, in addition to the conditions for the permissibility of polygamy because the wife's condition is not found explicitly in the texts or opinions of traditional fiqh scholars. This study utilizes a comparative descriptive approach by analyzing the history, legal basis, and views of Madhab scholars regarding polygamy, as well as comparing the application of polygamy regulations in Asian and African countries (Indonesia, Malaysia, Pakistan, Morocco, and Tunisia). The results show that the reasoning behind polygamy regulations set in modern Muslim countries in Asia and Africa seems to be more dominant using the extra-doctrinal reform method. This cannot be separated from the goals of family law reform, the effort to unify law in a heterogeneous society, demands to increase women's status, and respond to community developments. The background factors include the influence of the colonizers, reinterpretation of the texts and madhabs adopted, and other geopolitical factors.